SINTESIS DAN ANALISIS HUBUNGAN KUANTITATIF STRUKTUR AKTIVITAS (HKSA) SENYAWA TURUNAN METRONIDAZOLE-PIPERAZINE SEBAGAI ANTIGIARDIASIS: SYNTHESIS AND QUANTITATIVE STRUCTURE ACTIVITY RELATIONSHIP ANALYSIS (QSAR) OF METRONIDAZOLE-PIPERAZINE DERIVATIVES AS ANTIGIARDIASIS - Khairunnisa Khairunnisa; Najma Annuria Fithri; Novilia Megi Annisa; Riza Indah Sari; Putri Rahayu Oktalia; Hexes Wianchi (JFL : Jurnal Farmasi Lampung, 2026)
This study aimed to synthesize and evaluate the quantitative structure–activity relationship (QSAR) of a series of metronidazole–piperazine derivatives as potential antigiardiasis candidates. Electron-withdrawing (EWG) and electron-donating (EDG) substituents were modified on the piperazine nitrogen group to observe their effects on biological activity in silico. Descriptor analysis was performed using 12 physical, electronic, and topological parameters of the molecule. QSAR modeling was performed using multiple linear regression (MLR) using the Leave One Out (LOO) method. Model validation showed a Q² value of 0.9768, R = 0.99, and a low RMSEC, indicating the model is stable and suitable for use as a predictor. The final HKSA equation obtained is Y’ (log 1/C) = 15.620779 + 0.00125(chi1v) + 0.002787(dipole) + 32.525224(glob) + (-3.4999394) (mr)+ (-0.001002) (logP(o/w)) + 4.878564(PEOE_PC+) + (-1.619287) (PEOE_PC-) + 0.000150(pmi) + (-0.046015) (TPSA) + 0.000125 (Zagreb) + 1.025935(AM1_HOMO) + -0.907413(AM1_LUMO). Molecular docking results against the ferredoxin oxidoreductase receptor indicated that 2a was the ligand with the best binding affinity, thus predicting it as the most potential candidate for antigiardiasis compared to other compounds. Compound 2a exhibited quite good biological activity with a value of 1.052 µg/cm³.   Keywords: metronidazole-piperazine, QSAR analysis, compound synthesis, compound 2a